2015
DOI: 10.1371/journal.pone.0138114
|View full text |Cite
|
Sign up to set email alerts
|

Chorioamnionitis and Patent Ductus Arteriosus: A Systematic Review and Meta-Analysis

Abstract: BackgroundChorioamnionitis has recently been reported as a risk factor for various neonatal diseases, including cerebral palsy, bronchopulmonary dysplasia, and necrotizing enterocolitis, but its effect on patent ductus arteriosus (PDA) is unclear. We performed a systematic review and meta-analysis to evaluate the effect of chorioamnionitis on PDA.MethodsWe searched PubMed, EMBASE, Cochrane Library, and KoreaMed databases using the terms: “intrauterine infection” or “maternal infection” or “antenatal infection”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 49 publications
1
56
2
2
Order By: Relevance
“…Prenatal corticosteroid prophylaxis decreases the risk for PDA [14,16,49,54,55], even if administered after chorioamnionitis [24]. In the present study, similar proportions of infants with and without PDA received prenatal corticosteroids, and even if more infants received a complete course, the difference between the two groups was not significant p>0.050.…”
Section: Patent Ductus Arteriosus Associated Risk Factors and Cliniccontrasting
confidence: 41%
See 4 more Smart Citations
“…Prenatal corticosteroid prophylaxis decreases the risk for PDA [14,16,49,54,55], even if administered after chorioamnionitis [24]. In the present study, similar proportions of infants with and without PDA received prenatal corticosteroids, and even if more infants received a complete course, the difference between the two groups was not significant p>0.050.…”
Section: Patent Ductus Arteriosus Associated Risk Factors and Cliniccontrasting
confidence: 41%
“…They also found that antepartum haemorrhage occurred more often in premature infants with PDA. Many studies linked chorioamnionitis to PDA in preterm infants [3,15,[23][24][25]56]. In these cases, inflammation increases cyclo-oxygenase activity and prostaglandin E2 production causing PDA [56].…”
Section: Patent Ductus Arteriosus Associated Risk Factors and Clinicmentioning
confidence: 99%
See 3 more Smart Citations